The role of visual imagery in cognition - Rimkutė, Eglė (Psichologija, 1977)
The article deals with the works of contemporary authors who analyse the role of visual imagery in verbal learning, detection of the signals, recall of the visual material. The works devoted to the research of the influence of subjective vividness of imagery on the effectiveness of different kinds of cognition are considered.